Evaluation of the abuse potential of difelikefalin, a selective kappa‐opioid receptor agonist, in recreational polydrug users - Megan J. Shram; Robert H. Spencer; Jenny Qian; Catherine L. Munera; Michael E. Lewis; Jack E. Henningfield; Lynn Webster; Frédérique Menzaghi (Wiley, 2022)
Abstract Difelikefalin, a selective kappa‐opioid receptor agonist with limited central nervous system penetration, is being developed for the treatment of chronic pruritic conditions. This randomized, double‐blind, active‐ and placebo‐controlled, four‐way crossover study was designed to evaluate the abuse potential of difelikefalin in healthy recreational polydrug users. Using a 4 × 4 Williams design, nondependent adult users of opioids and hallucinogens (N = 44) were randomized to receive single intravenous (i.v.) injections of difelikefalin at supratherapeutic doses (5 and 15 mcg/kg); pentazocine (0.5 mg/kg), a schedule IV mu‐opioid partial agonist and kappa‐opioid receptor agonist; and placebo. The abuse potential of difelikefalin was compared with pentazocine and placebo using the maximal score (maximum effect [Emax]) of the Drug Liking visual analog scale (VAS; primary end point), along with multiple secondary end points of subject‐rated measures and pupillometry. Difelikefalin produced significantly lower Drug Liking VAS Emax, and lower peak positive, sedative, and perceptual effects compared with pentazocine. These effects of difelikefalin were small, brief, and not dose‐dependent, although marginally greater than those observed with placebo. Neither dose of difelikefalin elicited significant negative or hallucinogenic effects. On end‐of‐session measures of overall drug liking and willingness to take the drug again, difelikefalin did not differ from placebo, indicating subjects neither liked nor disliked the effects overall and did not feel motivated to take the drug again. Consistent with its lack of mu agonist activity, difelikefalin did not induce miosis compared with pentazocine. All treatments were generally well‐tolerated. This study indicates that difelikefalin presents a low potential for abuse.